PO040 Breakthrough seizures – further analysis of the sanad study. (1st December 2017) - Bonnett, Laura; Powell, Graham; Smith, Catrin Tudur; Marson, Anthony
Abstract : Background: A breakthrough seizure is one occurring after at least 12 month remission whilst on treatment. Prognostic models for risk of breakthrough seizure, risk of seizure recurrence after breakthrough seizure, and likelihood of achieving 12 month remission following a breakthrough seizure are developed. Methods: SANAD compared treatments for patients with newly diagnosed epilepsy. Multivariable regression modelling was used to investigate how clinical factors affect the probability of each outcome. Results: Neurological insult, number of tonic-clonic seizures by achievement of 12 month remission, and time taken to achieve 12 month remission were significant factors for risk of breakthrough seizure. Total number of drugs attempted to achieve 12 month remission, time to achieve 12 month remission prior to breakthrough seizure, and breakthrough seizure treatment decision were significant for risk of seizure recurrence following a breakthrough seizure. Gender, age at breakthrough, time to achieve 12 month remission prior to breakthrough, and breakthrough seizure treatment decision were significant for likelihood of achieving 12 month remission after a breakthrough seizure. Conclusions: These models help to identify patients most likely to have a breakthrough seizure, to have a recurrence following a breakthrough, and to achieve 12 month remission following a breakthrough. This will aid individual patient risk stratification and the design of future epilepsy trials.